Bottled Water Consumption Habits and Purchase Behaviours of Consumers in the Urban Areas of Adana - Mutlu Bulut; Arzu Seçer (Turkish Journal of Agriculture: Food Science and Technology, 2019)
In recent years, the world population, urbanization process and need for natural water resources have increased. Therefore, providing the safe and clean drinking water has become an important topic of our day. This research was carried out to determine the bottled water consumption habits and purchasing behaviours of consumers. Primary data were obtained from 384 consumers living in urban areas of Adana province. The demographic characteristics and consumption habits of consumers were determined by calculating frequencies, ratios and averages. Factor analysis was used to determine the factors that affect the purchasing behaviours of the consumers and the cluster analysis were used to distinguish consumers with different perception levels from those with similar characteristics. Results indicated that 40.4% of participants consumed bottled water and 85.2% of these consumers took into account the brand of bottled water. Factor analysis revealed that 3 factors, product characteristics, packaging and price, and recognition affected purchasing behaviours in this sample. As a result of the K-means clustering analysis consumers in this study were divided into 3 groups. The most important factors for consumers in these observed clusters were shelf life, product freshness and product hygiene.